Enhancing the Indonesia Air Defense System. The immediate and urgent application of GCI Radar in safeguarding the airspace sovereignty of the Republic of Indonesia - Joesoef, Norman; Risman, Helda; Hadianto, Muhammad (Technium Social Sciences Journal, 2022)
This journal is prepared as a sequel to the first journal with title Enhancing the Indonesia Air Defence Systems: Confronting the challenges and military build-up In the Indo Pacific region. The first journal was focused on the threat faced by the Indo-Pacific region with the rise of Chinese military dominance, and the study to counter the threats through effective effectors such as the Air Defence Missile. Further to this background, this journal subtitled, The immediate and urgent application of GCI Radar in safeguarding the airspace sovereignty of the Republic of Indonesia, will focus on the supplement systems to safeguard the aerial sovereignty of the Republic of Indonnesia through the additional fielding of Ground Control Interceptor Radar Complex. 21st century battlefield landscape have much changed since the last World War, and again it has proven so dramatically important to keep the air dominance over defended territory. Therefore, not only the ability to defend and to neutralise a target, it is imperative that in order to defend, there must be a modern systems that can object, discriminate, and track an agressor to guide military decision makers in any given operation. This journal is prepared to supplement a comperhensive study of future possible conventional military engagements over the Indo-Pacific region with China and Indonesia at its main focus.